Penerapan Akad Murabahah Dalam Produk Pembiayaan Bagi Pensiunan di BSM KCP Bondowoso - Uddin, Amin (Universitas Muhammadiyah Surabaya, 2019)
This study examines the application of murabahah contracts on pension financing products conducted at Bank Syariah Mandiri KCP Bondowoso between the bank and its customers based on DSN-MUI fatwa Number 4 of 2000 concerning murabahah financing and DSN-MUI fatwa Number 88 of 2013 concerning General Guidelines for Program Implementation Pension Based on Sharia Principles. The problems that will be answered through this research are: (1) How is the application of the murabahah contract to pension financing products in Bank Syariah Mandiri KCP Bondowoso? (2) What is the DSN-MUI fatwa review of the application of the murabahah contract to pension financing products at Bank Syariah Mandiri KCP Bondowoso? This research is field research, because research activities are conducted at Bank Syariah Mandiri KCP Bondowoso. The research approach used is a qualitative descriptive research approach. To understand and analyze the object under study, the author uses several approaches such as the legislative approach and the comparative approach. Data collection techniques using observation, documentation, and interview techniques. While the data analysis technique uses a comparative analysis method.The results of this study are: (1) The pension financing contract in Bank Syariah Mandiri KCP Bondowoso is carried out by using a murabahah contract by fulfilling the following conditions: (1) The contract is done by reciting ijab and qabul; (2) Contracts are clearly implemented; (3) The object of the contract has been fully owned by the bank before being offered to prospective customers; (4) Contracts are carried out by prospective customers and the bank voluntarily without any coercion or threat; and (5) Contract objects are goods that are not prohibited by sharia. In the event of default, the bank will carry out billing steps by sending a notification letter, collection letter, warning letter 1 to 3. If the customer becomes bankrupt, the Bank will give up the time when it is able to settle its obligations if the business is bankrupt in an agreement the bank with the customer at the time of the murabahah agreement. (2) In general, the application of murabahah contracts to pension financing products at Bank Syariah Mandiri KCP Bondowoso is in accordance with the DSN-MUI fatwa, both DSN-MUI fatwa Number 4 of 2000 concerning Financing of Murabahah, and DSN-MUI fatwa Number 88 of 2013 concerning Guidelines General Implementation of Sharia Principles Based Pension Programs.Â Keywords: Fatwa, DSN-MUI, Murabahah, Pension, Bank Syariah Mandiri.